Miriam S. Taylor, Anti-Judaism and Early Christian Identity. A Critique of the Scholary Consensus, Studia Post-Bibiica 46, Leiden - New York – Köln 1995, E. J. Brill, ss. 208 - Bejda, Wojciech (Vox Patrum, 2000)
review